2010
DOI: 10.2217/pgs.09.158
|View full text |Cite
|
Sign up to set email alerts
|

Haplotypes of the Adrenergic System Predict the Blood Pressure Response to β-Blockers in Women with Essential Hypertension

Abstract: Our study confirmed the sex-specific association of GNB3 with the blood pressure response to atenolol with no substantial advantage of the analysis of haplotypes over SNPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…However, negative studies, including larger, well-powered investigations, predominate suggesting that rs1801253 cannot reliably predict antihypertensive response, rate control, or heart failure outcomes 11,17,[53][54][55][56][57][58] .…”
Section: Candidate Pharmacodynamic Polymorphisms Of Adrenergic Responsementioning
confidence: 99%
See 1 more Smart Citation
“…However, negative studies, including larger, well-powered investigations, predominate suggesting that rs1801253 cannot reliably predict antihypertensive response, rate control, or heart failure outcomes 11,17,[53][54][55][56][57][58] .…”
Section: Candidate Pharmacodynamic Polymorphisms Of Adrenergic Responsementioning
confidence: 99%
“…A single trial suggested the C allele of variant rs5443 is associated with improved SBP response to atenolol 54 . This trial suggested that two additional SNPs, rs11064426 and rs2301339, were also associated with atenolol response.…”
Section: Candidate Pharmacodynamic Polymorphisms Of Adrenergic Responsementioning
confidence: 99%
“…However, no significant genotype based effects of ADRB1 Ser49 and Arg389 polymorphism have been observed with dobutamine (Aquilante et al, 2008) or fluoxetine and paoxetine in Caucasian Americans (Turner et al, 2008). ADRB1 Ser49Gly and Arg389Gly and ADRB2 Cys19Arg, Gly16Arg and Gln27Glu polymorphisms were also not found to significantly affect BP response to Atenolol (Filigheddu et al, 2010). In contrast, Pacanowski et al (2008) found Ser49Gly and Arg389Gly to be significantly associated with response to atenolol in a study of 5,979 patients from 184 sites in the United States and Puerto Rico.…”
Section: β-Blockersmentioning
confidence: 94%
“…Three SNPs in the GNB3 gene, A3882C, G5249A and C825T have been found to have a significant effect on blood pressure response to atenolol in the female participants in Caucasian Americans (Filigheddu et al, 2010). Carvedilol is a non-selective and blocker that reduces the BP by blocking the binding of Norepinephrine to 1-and 2-adrenergic receptors (Stafylas & Sarafidis, 2008).…”
Section: β-Blockersmentioning
confidence: 99%
“…These studies investigated the association of RAS gene polymorphisms and responses to antihypertensive drugs, including angiotensin I-converting enzyme inhibitors (ACEIs), 13 angiotensin II receptor blockers (ARBs), 14 beta blockers 15 and diuretics. 16 Our group also endeavored to clarify the susceptible gene polymorphisms to thiazide diuretics 17 and calcium channel blockers (CCBs) 18 by candidate genes approaches, although there are very limited reports about gene polymorphisms associated with the effects of CCBs.…”
Section: Current Trends In Pharmacogenetic/ Pharmacogenomic Studies Omentioning
confidence: 99%